2011
DOI: 10.1139/y11-088
|View full text |Cite
|
Sign up to set email alerts
|

Flavokawain B induces apoptosis of human oral adenoid cystic cancer ACC-2 cells via up-regulation of Bim and down-regulation of Bcl-2 expression

Abstract: Novel effective drugs are still urgently needed in the prevention and treatment of oral adenoid cystic carcinoma (ACC). In this study, we have assessed the antitumor potential and molecular mechanisms of flavokawain B (FKB) as a kava chalcone on the ACC-2 cell line in vitro. The results demonstrated that FKB could significantly inhibit the cell proliferation of ACC-2 in a dose-dependent manner that was associated with induced apoptosis and cell cycle G2-M arrest, and the half maximal inhibitory concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Bcl-2 inhibits the realease of cytochrome c against Bax. The disturbance of Bcl-2/Bax protein ratio has been recognized as a factor contributing to the FKB-induced apoptosis [6,20]. In the present study, the increase in Bax and decrease in Bcl-2 was observed in both OS cell lines.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Bcl-2 inhibits the realease of cytochrome c against Bax. The disturbance of Bcl-2/Bax protein ratio has been recognized as a factor contributing to the FKB-induced apoptosis [6,20]. In the present study, the increase in Bax and decrease in Bcl-2 was observed in both OS cell lines.…”
Section: Discussionsupporting
confidence: 67%
“…The consumption of kava root extracts in the Pacific Islands has been associated with a lower incidence of cancer [4]. Extracts of kava are classified into two main classes of compounds: kavalactone and chalcone [5,6]. Chalcones have shown anticancer activity via inhibition of cell proliferation, carcinogenesis and metastasis [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, epidemiological studies illustrated that populations that consume the kava beverage have low incidences of cancer, compared to non-kava-drinking populations (Steiner 2000;Agarwal and Deep 2008). Extracts of kava are classified into two main classes of compounds kavalactone and chalcone, and flavokawain B belongs to chalcone compounds (Warmka et al 2012;Zhao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between autophagy and apoptosis is complex and varies with cell category, cell condition and stimulation . Accumulating evidences suggest that there is a mechanistic overlap between apoptosis and autophagy . Thus, researchers are interested in signalling pathways that regulate both autophagy and apoptosis.…”
Section: Introductionmentioning
confidence: 99%